Sanselige Verdener. Poetik Og Repræsentation I Dea Trier Mørchs Rejsebøger - Schab, Sylwia Izabela (Folia Scandinavica Posnaniensia, 2014)
The article deals with three travel books (Sorgmunter socialisme (1968), Polen (1970) and Da jeg opdagede Amerika (1986)) written by a Danish graphic designer, writer and political activist Dea Trier Mørch (1941-2001). In focus of the text analysis is the question of poetological aspects, a.o. of the position of the three texts in relation to travel books as a genre and the narrative strategies, which are used by the author to represent the visited countries. As the analysis will reveal, Mørch (as author and protagonist) can be understood as a modern sentimental traveler - both in terms of the structure of her narratives and the existential dimension of her travels.